2018
DOI: 10.1002/ijc.31752
|View full text |Cite
|
Sign up to set email alerts
|

Toward a real liquid biopsy in metastatic breast and prostate cancer: Diagnostic LeukApheresis increases CTC yields in a European prospective multicenter study (CTCTrap)

Abstract: Frequently, the number of circulating tumor cells (CTC) isolated in 7.5 mL of blood is too small to reliably determine tumor heterogeneity and to be representative as a "liquid biopsy". In the EU FP7 program CTCTrap, we aimed to validate and optimize the recently introduced Diagnostic LeukApheresis (DLA) to screen liters of blood. Here we present the results obtained from 34 metastatic cancer patients subjected to DLA in the participating institutions. About 7.5 mL blood processed with CellSearch® was used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 29 publications
1
96
0
Order By: Relevance
“…Importantly, none of the patients experienced adverse effects (mild, moderate, or severe). It is of note that since our initial description, DLAs have been carried out in different European hospitals without adverse effects (12,13). The reported mild adverse events are mainly due to (17) and usually occur after longer periods of leukapheresis (e.g., >2-3 h).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Importantly, none of the patients experienced adverse effects (mild, moderate, or severe). It is of note that since our initial description, DLAs have been carried out in different European hospitals without adverse effects (12,13). The reported mild adverse events are mainly due to (17) and usually occur after longer periods of leukapheresis (e.g., >2-3 h).…”
Section: Discussionmentioning
confidence: 95%
“…It was calculated that the probability to detect at least one of 1,000 CTCs in 5 l circulating blood (≤1.5 CTC/7.5 ml) with CS is just 34% due to Poisson statistics, assay efficacy of 80 (AE15)%, and an inter-reader variability of 0.8 (16). But promising depletion strategies are underway enabling to analyze at least a large part of the product (12). Therefore, analyzing 5% of DLA products, which was equivalent to a median PB volume of around 60 ml, boosted already the detection probability in the M0 patients that often have less than 1,000 CTC circulating in their total blood volume (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extrapolation of the frequency distribution of CTC in patients with metastatic prostate cancer, breast, and colorectal cancer showed that an increase of blood volume from 7.5 ml to 600 ml >90% of patients with metastatic cancers will have CTC detected (33). However, at present the available technologies are not yet capable of isolating CTC from the complete DLA volume (34)(35)(36). This procedure baptized Diagnostic Leukapheresis indeed allows for the isolation of a substantial larger number of CTC and enables a true "liquid biopsy."…”
mentioning
confidence: 99%